5(x+1)-(-3x+1)=2(3x+5)10x=

Simple and best practice solution for 5(x+1)-(-3x+1)=2(3x+5)10x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+1)-(-3x+1)=2(3x+5)10x= equation:



5(x+1)-(-3x+1)=2(3x+5)10x=
We move all terms to the left:
5(x+1)-(-3x+1)-(2(3x+5)10x)=0
We multiply parentheses
5x-(-3x+1)-(2(3x+5)10x)+5=0
We get rid of parentheses
5x+3x-(2(3x+5)10x)-1+5=0
We calculate terms in parentheses: -(2(3x+5)10x), so:
2(3x+5)10x
We multiply parentheses
60x^2+100x
Back to the equation:
-(60x^2+100x)
We add all the numbers together, and all the variables
8x-(60x^2+100x)+4=0
We get rid of parentheses
-60x^2+8x-100x+4=0
We add all the numbers together, and all the variables
-60x^2-92x+4=0
a = -60; b = -92; c = +4;
Δ = b2-4ac
Δ = -922-4·(-60)·4
Δ = 9424
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{9424}=\sqrt{16*589}=\sqrt{16}*\sqrt{589}=4\sqrt{589}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-92)-4\sqrt{589}}{2*-60}=\frac{92-4\sqrt{589}}{-120} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-92)+4\sqrt{589}}{2*-60}=\frac{92+4\sqrt{589}}{-120} $

See similar equations:

| 12b=2 | | 3.5x+0.5x=18+4.5x | | 103+4y+12=180 | | 6s=270 | | 0=-t^2+18t | | -3(4x-5)+2x-1=24 | | 3x+12=2(x‒3) | | -3(x+1)+4=-3x10+11x-17 | | 6x2x=4 | | x=360-172 | | 32x=20x+23 | | 4x-3(x+5)=2(x+3) | | 32x+20x+23=180 | | -3+2r=-13 | | 32+20x+23=180 | | -5m+5=35 | | 5(×-6)=2(x+3) | | 10(x+2)-8x=12 | | x2+8x=2 | | m2=( | | h/6-5=-3 | | -8+3w=15-2w | | 9x^2-8=19 | | y=8+15 | | y-3=24-2y | | 180=-6(5+7x) | | 2u-9=9u+24 | | -2x+7=6.5 | | 2x+6−5x=−3(x− | | (2x+11)=(3x+4) | | 4x+8.6=50 | | 3(2x+10)+6=0 |

Equations solver categories